Distribuição de renda no Brasil: uma análise entre 1995 e 2009 - Carrara, Vagner (2011)
The aim of this study is to analyze the evolution of income distribution in Brazil between 1995 and 2009. Basically, the literature research was adopted as research procedure. To enhance understanding of this task a theoretical basis about income distribution is presented, as well as a historical background to the early 1990s, and an investigation of the economic and social policies adopted by successive governments in the reference period. The first result is the stability of inequality in income distribution during the 1990s, derived mainly from the present difficulties in the labor market, the fruit of productive restructuring and the economic policies adopted, particularly the use of exchange rate policy to control inflation. The increase in social expending with the executions of the determinations of the Constitution of 1988, mainly social benefits, allowed this stability inequality. In the 2000s, fortunately, the income distribution had a significant improvement detected annually through the household survey (PNAD). The continued expansion of social expending through implementation of income transfer programs, the improvement of the minimum wage, and the recovery of formal jobs in the labor market explain a significant part of the fall of the indices of inequality. The income transfer policies, mainly from the Benefício de Prestação Continuada and the Bolsa Família programs, have increased the share of income not derived from labor in the formation of total income. The progressivity of this category of income and the reduction in the concentration of labor income were the main determinants of this improvement in income distribution